The Market Price of Risk, Size of Market and Investor's Risk Aversion: A Reply - Lintner, John (The Review of Economics and Statistics, 1972)
Where G is the geometric mean rate of return on the individual's net worth. W,k is the kth individual's initial wealth. Using this approximation, the market price of risk, 4)-1, is equal to HaIM. The inclividual investor's risk aversion is W11,-1, E(1 R1,) _ W*1,k, and HaIM (I W*1k)l. k Under the assumption that expected future prices are independent of current prices, the market price It may be noted that the Bernoulli utility function, unlike the quadratic and exponential utility of risk is unaffected by changes in the number of investors.